Metodologi tarannum al-Quran menurut bacaan Mustafa Isma'il (M. 1978) dan pengaruhnya di Malaysia / Khalid Isa - Khalid , Isa (2019)
This research focuses on Shaykh Mustafa Ismaï¿½il, an eminent figure in tarannum al-Quran. The discussion relates to the methods of tarannum al-Quran recitation and its influence in Malaysia. The main objectives of this research were to scientifically clarify the tarannum al-Quran and its manhaj in Malaysia, to unfold the background of Shaykh Mustafa Ismail, to study the methods in his tarannum recitation and to analyse his influence in Malaysia.The research was conducted through references from library and on-site study. The findings of the research exhibited that tarannum al-Quran is a Sunnah from Rasulullah (s.a.w) which has been evidenced based on several hadith sahih. Tarannum al-Quran manhaj in Malaysia can be divided into two parts; which are Hijazi Arabic tarannum and Misri Arabic tarannum. In term of recitation methods, it could be concluded that there are four main items involved: tarannum, voice, tajwid and qira?at. In reality, the recitation of Shaykh Mustafa Ismaï¿½il has influenced majority of the community in Malaysia. A comprehensive research on the influence of his recitation on two main aspects; which are writing and recitation among qari and qariah, has been conducted. Eventually, it can be summarized that the influence in writing could be recognized through several works and articles scattered all around Malaysia. The strong influence of Mustafa Ismaï¿½il?s recitation on the recitation of qari and qariah stemmed from the earliest tarannum scholar, Hj. Ahmad Mat Som Pergau who was a student of Mustafa Ismaï¿½il. He has instilled in his tarannum teaching to his students to follow the uslub or tariq of Shaykh Mustafa Ismail.